RISET EFEKTIFITAS EDUKASI DAN PENYULUHAN TENTANG PEMBALUT KAIN DALAM MENINGKATKAN KESADARAN LINGKUNGAN DI KALANGAN REMAJA DI DESA PASONGSONGAN KECAMATAN PASONGSONGAN KABUPATEN SUMENEP - Fitroh, Fitrotil inayah (ABDISUCI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Pasongsongan village, Pasongsongan subdistrict, Sumenep district is one of the villages with a fairly large waste problem, due to people's habit of throwing rubbish directly into rivers and the sea. Disposable sanitary napkin waste is also a big problem for Pasongsongan village, both sanitary napkins for women and even sanitary napkins for small children. This research uses a quantitative approach with data analysis using interview data with village heads and village women as local stakeholders, as well as surveys of village environmental conditions. The results of the analysis show that the habit of teenagers in Pasongsongan village in choosing sanitary napkins is using disposable sanitary napkins and the habit of disposing of community waste is throwing rubbish in rivers and the sea. The effectiveness of counseling and education in increasing environmental awareness among teenagers is very good and has succeeded in encouraging teenagers to use cloth sanitary napkins as an alternative to minimizing waste income starting from themselves. By implementing the recommendations from this research, it is hoped that Pasongsongan Village will experience an increase in awareness for every teenager to choose cloth sanitary napkins as their next sanitary napkin. It is also hoped that this research will provide guidance for other villages that face similar challenges regarding waste problems in their villages.